Manajemen Perpustakaan dalam Mengembangkan Budaya Literasi Siswa di SMP Swasta Pahlawan Nasional Medan - Wibowo, Muhammad Padeli; Budi, Budi (LPPM Institut Pendidikan Nusantara Global, 2025)
Literacy culture is a fundamental pillar in shaping a generation capable of critical thinking, creativity, and competitiveness. In the context of junior secondary education, the school library plays a strategic role in fostering literacy culture through various literacy programs and activities. This study aims to describe the library management in developing students’ literacy culture at SMP Pahlawan Nasional Medan, covering aspects of planning, implementation, organization, and evaluation of library programs. This research uses a qualitative approach with a case study method. Data were collected through observations, in-depth interviews with the principal, librarian, teachers, and students, as well as documentation of library activities. The results showed that library planning was carried out systematically, involving multiple stakeholders and aligned with students’ reading needs and interests. Implementation of literacy programs such as the Morning Literacy Movement and One Book One Month proved effective in increasing student engagement in reading and writing activities. The library organization functioned collaboratively with clear distribution of roles among involved parties. Program evaluation was conducted periodically and served as a basis for library development and improvement. Based on these findings, it can be concluded that library management at SMP Pahlawan Nasional Medan has been implemented effectively and contributes significantly to the development of students’ literacy culture.